Dysregulation of hypoxia pathways in fumarate hydratase-deficient cells is independent of defective mitochondrial metabolism. - O'Flaherty, L; Adam, J; Heather, L; Zhdanov, A; Chung, Y; Miranda, M; Croft, J; Olpin, S; Clarke, K; Pugh, C; Griffiths, J; Papkovsky, D; et al. (2010)
Mutations in the gene encoding the Krebs cycle enzyme fumarate hydratase (FH) predispose to hereditary leiomyomatosis and renal cell cancer in affected individuals. FH-associated neoplasia is characterized by defective mitochondrial function and by upregulation of transcriptional pathways mediated by hypoxia-inducible factor (HIF), although whether and by what means these processes are linked has been disputed. We analysed the HIF pathway in Fh1-/- mouse embryonic fibroblasts (MEFs), in FH-defective neoplastic tissues and in Fh1-/- MEFs re-expressing either wild-type or an extra-mitochondrial restricted form of FH. These experiments demonstrated that upregulation of HIF-1alpha occurs as a direct consequence of FH inactivation. Fh1-/- cells accumulated intracellular fumarate and manifested severe impairment of HIF prolyl but not asparaginyl hydroxylation which was corrected by provision of exogenous 2-oxoglutarate (2-OG). Re-expression of the extra-mitochondrial form of FH in Fh1-/- cells was sufficient to reduce intracellular fumarate and to correct dysregulation of the HIF pathway completely, even in cells that remained profoundly defective in mitochondrial energy metabolism. The findings indicate that upregulation of HIF-1alpha arises from competitive inhibition of the 2-OG-dependent HIF hydroxylases by fumarate and not from disruption of mitochondrial energy metabolism.